The End of the End of History: A Political-Economy Perspective - Ben Zissimos (Intereconomics, 2022)
From the standpoint of the focus of this article, we need to find a better way to compensate the losers from globalisation so that voters re-engage through the democratic process with openness and benefit from the potential for increased prosperity that this holds.
Keywords: N40; F52; F55; 330